Primary Adrenal Lymphoma: Two Case Series From China - Zeng, Jinyang; Yan, Fangfang; Chen, Yulong; Zang, Li; Chen, Kang; Lyu, Zhaohui; Dou, Jingtao; Mu, Yiming; Lin, Mingzhu; Yang, Guoqing (Frontiers in Endocrinology, 2022)
Objective: Primary adrenal lymphoma (PAL) is a rare entity of adrenal mass, here we summarize our experience in the clinical presentation, biochemical indexes, radiological features, pathological information, therapy regimens and outcomes of PAL. Methods: This was an IRB approved retrospective review of medical records and surgical pathology specimens of patients with a diagnosis of primary adrenal lymphoma at Chinese People's Liberation Army general hospital and the first affiliate hospital of Xiamen University between July 2007 to July 2017. Results: 26 Patients were identified. The age at presentation were 60.84±13.14 years with a male-to-female ratio of 2.25:1(18:8). The most common presenting symptoms were loss of appetite(65%, 17/26), weight loss(62%, 16/26), abdominal pain(58%, 15/26) and fatigue(58%, 15/26). The levels of Lactate Dehydrogenase(75%, 15/20), β2-microglobulin(100%,10/10), C-reactive protein(82%, 14/17), Erythrocyte Sedimentation Rate(83%, 10/12), Ferritinaemia(88%, 7/8) were elevated. Bilateral involvement was seen in 21 of 26 patients(81%), 12 of 19 bilateral lesion patients(63%) were confirmed as adrenal insufficiency. On CT scan, the mean diameter was 7.31±3.35cm and median Hounsfield density were 37.0HU(range: 31.0–45.0), 67%(10/15) and 27%(4/15) of leisions presented as mild and moderate enhancement after injection of contrast medium. 18F-FDG PET-CT not only revealed the adrenal tumor but also extra-adrenal lesion. Diffuse large B cell lymphoma (DLBCL) was the most common phenotype(92%, 24/26). 92%(24/26)of patients received chemotherapy while 8%(2/26) of our cases received unilateral adrenalectomy plus chemotherapy. The prognosis of PAL was poor, with a general survival time of 7.20±5.18 months. Conclusion: PAL is a rare disease. The clinical characteristics of PAL include loss of appetite and weight loss. Endocrine evaluation should be performed to determine whether the patients have adrenal insufficiency, especially bilateral lesion patients. FDG-PET appears to be more accurate than other imaging to reveal extra-adrenal sites. Better therapy is required to improve the outcome due to the poor prognosis of PAL.